Propuesta de implementación del sistema de gestión ambiental bajo los requisitos de la norma técnica colombiana NTC ISO 14001: 2015 para la empresa Prevención en Riesgos Operativos S.A.S en la ciudad de Bogotá (2021)
The main objective of this document is the diagnosis, formulation and action plans for the structuring of the design of the Environmental Management System NTC ISO 14001: 2015 in the company PREVENCION EN RIESGOS OPERATIVOS SAS, which to date lacks the implementation of environmental management programs, the company offers the national industry comprehensive and innovative solutions on issues related to safety, health at work and environmental management within its production processes handle the manufacture and marketing of products and services oriented to these specific areas.